Rumah Sakit Umum Kelas C Di Pulau Rupat Dengan Pendekatan Healing Environment - Octa Farnas; Wahyu Hidayat; Mira Dharma Susilawati (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Rupat Island is one of the districts in Bengkalis Regency, Riau Province. Rupat Island area is fairly wide with a large population that has not had a single hospital, but only in the form of puskesmas, and non-inpatient health facilities. For that, the need for health facilities for people in Rupat Island is by providing hospitals. The purpose of this research is to design Class C General Hospital by applying the elements and principles of Healing Environment. The methods used include field data collection, literature study and empirical studies. The application of Healing Environment theme in Class C General Hospital in Rupat Island is considered to be in harmony because Rupat Island still has good environmental quality and the main function of the building as a health facility. General Hospital Design with Healing Environment approach directed more specifically with the use of the concept of Healthy With Nature. The mass concept resulted from the influence of natural environment conditions around the tread that has more potential and is supported by consideration of natural elements such as light, air, and plants. So the design result that makes residents can access and interact with nature directly.Keywords: Rupat Island, Hospital, Healing Environment.